El rol de la familia y su impacto en el aprovechamiento de los niños de inicial 2 de la unidad educativa Simón Rodríguez, parroquia Licán, cantón Riobamba. - Novillo Ríos, Génesis Gabriela (2025)
This research aims to highlight the importance of family in the holistic development of children during their early years of life. In this context, on its primary conception, the family is understood as the primary influence on upbringing in early childhood, shaping the way a child will develop throughout their life, influencing patterns, behaviors, preferences, and more. Achievement is viewed as the level of skills and abilities acquired throughout the teaching and learning process, which is assessed not only quantitatively but also by considering different areas of development, relative to the child's age. The objective of this study is to analyze the role of the family in children's academic achievement. A mixed-methods approach was employed, using a field, bibliographic, and transversal study design. The research technique was observation, with an observation checklist applied to both parents and children. The study focused on a sample of 25 students from the second grade of early childhood education (section “A”) at Simón Rodríguez School. The results of the research suggest that the presence of a caregiver during early childhood is crucial for student achievement. The academic and social performance of children is significantly correlated with the level of interest and involvement shown by their caregivers.